Thyroid-like follicular carcinoma of kidney: case presentation and literature review - Ameer Afzal; Ahmad kaleem; Mohammad Sohail Asghar; Mohammad Sohaib Asghar (Journal of the Pakistan Medical Association, 2021)
Published in August 2021